How physical activity opportunities seized by adolescents differ between Europe and the Pacific Islands: the example of France and New Caledonia [version 1; peer review: 2 approved] - Olivier Galy; Guillaume Wattelez; Francois Potdevin; Marie-Jeanne Urvoy; Thibaut Derigny; Paul Zongo; Pierre-Yves Leroux; Christophe Schnitzler (Open Research Europe)
Background France (FR) and New Caledonia (NC) are both French territories, one in Western Europe, the other as part of the Pacific Island Countries and Territories (PICTs). Despite schooling in similar educational systems, FR and NC adolescents develop distinct relationships with physical activity, which is influenced by the geographical-cultural and symbolic structures of their respective societies. This study explored the distribution of physical activity according to geographical culture and opportunity-temporal dimensions. Methods Participants were randomly selected, with individual (boys vs. girls), spatial (rural vs. urban), and geographical (FR vs. NC) stratifications. Accelerometers GT3X (ActiGraphTM, Pensacola FL, USA) and daily logbooks were used to measure the physical activity intensity and opportunities during the week. Results A total of 156 participants were included in this study. A significant effect was found in moderate to vigorous physical activity (MVPA) intensity with the geographical-cultural dimension; participants living in FR were more likely to engage in MVPA, especially in five opportunities: school, supervised leisure, home, school breaks, and transport. For both FR and NC adolescents, physical education lessons had the highest MVPA. Conclusion This study showed that MVPA differed in the same national educational system according to geographical culture. Physical education lessons could catch the challenge of an “opportunity education” (opportunities are defined as temporal invitations to engage in PA) by opening the door to two particular opportunities: supervised leisure and active transport.